A luta por uma identidade: uma etnografia sobre a subcultura de consumo de MMA - Silveira, Isabel da Costa (2011)
The purpose of this dissertation is to identify how the subculture belonging to the MMA influence in shaping the identity of their members, exploring the aspects related to the consumption as a vehicle for transmission of symbolic meanings. The theoretical foundation which has supported the research addresses issues discussed in the literature with regard to culture and consumption (Barbosa and Campbell, 2006; McCracken, 2003), the subcultures of consumption (Kozinets, 2001, Schouten and McAlexander, 1995), and to the process of identity formation through consumpt ion (Barbosa and Campbell, 2006; McCracken, 2003). This study has exploratory and an explanatory nature , searching through the ethnographic method to explore the cultural universe that works as the background of the questions addressed and then identify the factors that determine or contribute to the process of identity formation in a subculture of consumption. Data were collected over one year of field research, carried out in a martial arts academy in Rio de Janeiro. During the research , it was possible to collect informat ion about the day-by-day of members of this subculture and the relationships that are formed from this consumer activity. Also individual interviews were conducted from a semi-structured script, aiming at understanding how these consumers find themselves within the subculture and how interprets the MMA as a lifestyle and provider of values . 14 interviews were conducted with consumers both female and male, between the ages of 19 and 45 years living in the city of Rio de Janeiro, between January and November 2011. In order to achieve the proposed objectives, a qualitative research method was chose, focusing on the comprehension of the meanings of the facts, through analysis of small samples of the population, trying to understand the facts without necessarily measure them. The results showed that being part of a subculture doesn’t necessarily imply the creation of an identity based on the object of consume. Some steps need to be fulfilled, and in the case of MMA, not just the commitment: to be accepted by the group, demonstrate specific skills and make a proper use of the fight are, for example, basic requirements for achieving new positions within the subculture, and thus gain an identity representative of this group.